1995
DOI: 10.1002/cne.903550202
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergin innervation of the primate hippocampal formation. I. Distribution of choline acetyltransferasse immunoreactivity in the Macaca fascicularis and Macaca mulatta monkeys

Abstract: The cholinergic innervation of the hippocampal formation of Macaca fascicularis (cynomolgus) and Macaca mulatta (rhesus) monkeys was investigated by immunohistochemical procedures using a monoclonal antibody directed against choline acetyltransferase. The distribution of choline acetyltransferase in the monkey demonstrated both similarities and differences with the staining patterns observed in the rat or with acetylcholinesterase in the monkey. While both of these latter preparations demonstrated labeled cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 85 publications
3
44
0
Order By: Relevance
“…Some sections were processed following a double-bridging procedure by returning them to the secondary antiserum solution for 1 h after the incubation in PAP and then again to the PAP complex for 90 min. After this, the sections were developed, mounted, and intensified by immersion in aqueous solutions of 0.005% osmium tetroxide and 0.05% thiocarbohydrazide (Alonso and Amaral, 1995). DAT was revealed in monkey tissue using a standard DAB protocol (0.05% DAB and 0.003% H 2 O 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…Some sections were processed following a double-bridging procedure by returning them to the secondary antiserum solution for 1 h after the incubation in PAP and then again to the PAP complex for 90 min. After this, the sections were developed, mounted, and intensified by immersion in aqueous solutions of 0.005% osmium tetroxide and 0.05% thiocarbohydrazide (Alonso and Amaral, 1995). DAT was revealed in monkey tissue using a standard DAB protocol (0.05% DAB and 0.003% H 2 O 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…This result also may represent a synapomorphy, because lampreys, diverse teleosts, and amphibians uniformly lack ChAT-ir cells in pallial areas (Ekström, 1987;Brantley and Bass, 1988;Marín et al, 1997;Adrio et al, 2000;Pérez et al, 2000). Even in amniotes the presence of cortical cholinergic neurons seems to be a characteristic acquired relatively late during evolution and certainly is not a feature shared by all species (Vincent and Reiner, 1987;Reiner, 1991;Medina et al, 1993;Medina and Reiner, 1994;Alonso and Amaral, 1995).…”
Section: Secondary Prosencephalonmentioning
confidence: 95%
“…Studies of birds and reptiles have revealed the lack of cholinergic cells in cortical regions Brauth et al, 1985;Hoogland and Vermeulen-Van der Zee, 1990;Powers and Reiner, 1993;Medina and Reiner, 1994], with the lone exception of the lizard Gallotia gallotia [Medina et al, 1993]. In mammals, cholinergic cells were detected in the cortex of rats [Houser et al, 1985;Ichikawa and Hirata, 1986;Parnavelas et al, 1986;Ichikawa et al, 1997] and mice [Mufson and Cunningham, 1988;Consonni et al, 2009] but not in dogs, cats, guinea pigs, some rodents, monotremes [Kimura et al, 1981;Vincent and Reiner, 1987;Maley et al, 1988;St-Jacques et al, 1996;Manger et al, 2002;Bhagwandin et al, 2006] and adult primates, including humans Satoh and Fibiger, 1985;Mesulam and Geula, 1988;Geula et al, 1993;Alonso and Amaral, 1995]. Therefore, the presence of cholinergic cells in the pallium/cortex of vertebrates seems to be a variable feature that appears several times in evolution.…”
Section: Localization Of Chat-ir Elements In the Forebrain Of Holosteansmentioning
confidence: 99%